Management of Bronchial Asthma Through Herbo-Mineral Drugs (AYUSHDHARA, 2024)
Ayurveda is ancient system of medicine and a holistic approach to prevent and treat illness by maintaining balance in body and mind to improve your health and vitality. Ayurveda is one of alternative way of treating illness, prevention and management of respiratory disorders. Nowadays respiratory disorders are the major health issue resulting primary cause of death and disability in the world. Asthma is a common respiratory problem increasing globally and affecting approximately 339 million people worldwide and 17.23 million people with an overall prevalence of 2.05% in India. Bronchial asthma is a heterogeneous disease, usually characterized by chronic inflammatory disease of the airway. It is defined by chronic respiratory problem characterized by hyper-responsiveness, inflammation and narrowing of airway resulting in cardinal symptoms cough, chest tightness, dyspnea and wheeze. Tamak swasa closely resembles to bronchial asthma. Swasa roga is major health problem affecting the Pranavaha srotas. According to Acharya Charak tamak swasa is Vata-Kaphaja Vyadhi which is originated from Pithasthan (Amashaya). The treatment of this disease is still unsatisfactory in modern medicine as the use of corticosteroids have many side effects and may lead to medicine dependency. Ayurveda is proven to be a boon for management of asthmatic patients (Tamak swasa). Our Ayurveda classics have explained a lot about signs and symptoms of asthma that has a direct correlation with Tamak swasa. So this is the need of the time that a direct, safe and holistic approach should be established to treat the disease with specific herbomineral formulations as mentioned in our Ayurveda classics.